Indexing Odour by using electronic nose - Saiful Azhar, Saad; Mohd Noor, Ahmad; Ali Yeon, Md Shakaff; Suhardy, Daud; Farizul Hafiz, Kasim; Siti Nordiyana, Md. Salim; A.K.M. Shafiqul Islam (National Cheng Kung University, 2008)
Organized by National Cheng Kung University, 15th - 18th January 2006 at National Cheng Kung University, Taiwan.